2023
DOI: 10.1002/cam4.5742
|View full text |Cite
|
Sign up to set email alerts
|

Is tumor necrosis a clinical prognostic factor in hepato‐biliary‐pancreatic cancers? A systematic review and meta‐analysis

Abstract: Background It has been proven that tumor necrosis is associated with poor prognoses in various solid malignant tumors. However, the prognostic effect of tumor necrosis in hepato‐biliary‐pancreatic cancers is still unclear. Therefore, this study was performed to evaluate the associations of tumor necrosis with survival outcomes and clinicopathological features in patients with hepato‐biliary‐pancreatic cancers. Methods Based on the PRISMA statement, eligible studies were identified from PubMed, Embase, Cochrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 45 publications
0
0
0
Order By: Relevance
“…In a systematic review, the presence of tumor necrosis of solid tumors was reported for several entities, including breast, renal cell, non-small cell lung, and colorectal cancer, as a negative prognostic histopathological feature [4]. In the case of PDAC, a recent metaanalysis identified the detrimental prognostic role of tumor necrosis of the primary tumor in histopathology on overall survival (OS), recurrence-free survival, vascular and neural invasion, T stage, M stage, and grading [5][6][7][8]. Another recent study described a significant correlation of MRI-depicted tumor necrosis of PDAC to tumor size, nodal status, and metastases [9], while another study reported higher tumor grading and higher cellularity co-occurring with tumor necrosis determined by MRI [10].…”
Section: Introductionmentioning
confidence: 99%
“…In a systematic review, the presence of tumor necrosis of solid tumors was reported for several entities, including breast, renal cell, non-small cell lung, and colorectal cancer, as a negative prognostic histopathological feature [4]. In the case of PDAC, a recent metaanalysis identified the detrimental prognostic role of tumor necrosis of the primary tumor in histopathology on overall survival (OS), recurrence-free survival, vascular and neural invasion, T stage, M stage, and grading [5][6][7][8]. Another recent study described a significant correlation of MRI-depicted tumor necrosis of PDAC to tumor size, nodal status, and metastases [9], while another study reported higher tumor grading and higher cellularity co-occurring with tumor necrosis determined by MRI [10].…”
Section: Introductionmentioning
confidence: 99%